A gestão de resíduos da construção civil: iniciativas na bacia hidrográfica Tietê-Jacaré e uma proposta para o município de Bauru (SP) - Wiens, Ivy Karina [UNESP] (2008)
This research has as its main goal, study the situation of solid waste, specially construction and demolition waste, in the five largest cities in Tietê-Jacaré watershed, that is comprehended for 34 countries. Between 2006 and 2008 Araraquara, Bauru, Jaú, Lençóis Paulista e São Carlos received the field visit and a little deeper research. The used perspective was of the integrated environmental sanitation, as it is required by the federal law, which includes in this concept the water supply, the collecting and treatment of the sewer, the handling and final disposal of the solid residues and the urban drainage. The principles of the reduction, reutilization, recycling and recovery of the residues are inseparable from the effective management. As for the residues of the construction sector the promotion of differentiated management, in which the urban planning is used as a tool to optimize the application of the public resources is a tendency. Most of the time the city managers are not well prepared for this reality and then they need to act as articulators of the system involving all the protagonists - managers, transporters, generators, collectors. Experiments that have been successful in Brazil and abroad may be useful as examples, but each and every town must elaborate its own Management Plan properly adapted to the local reality. At the end of this study, it is a suggestion of a proposition for the implantation of an integrated management of the residues of the civil construction sector in the city of Bauru.